Arabidopsis fhl/fhy1 double mutant reveals a distinct cytoplasmic action of phytochrome A - Rösler, Jutta (National Academy of Sciences, 2007)
Phytochrome A (phyA) plays an important role during germination and early seedling development. Because phyA is the primary photoreceptor for the high-irradiance response and the very-low-fluence response, it can trigger development not only in red and far-red (FR) light but also in a wider range of light qualities. Although phyA action is generally associated with translocation to the nucleus and regulation of transcription, there is evidence for additional cytoplasmic functions. Because nuclear accumulation of phyA has been shown to depend on far-red-elongated hypocotyl 1 (FHY1) and FHL (FHY1-like), investigation of phyA function in a double fhl/fhy1 mutant might be valuable in revealing the mechanism of phyA translocation and possible cytoplasmic functions. In fhl/fhy1, the FR-triggered nuclear translocation of phyA could no longer be detected but could be restored by transgenic expression of CFP:FHY1. Whereas the fhl/fhy1 mutant showed a phyA phenotype in respect to hypocotyl elongation and cotyledon opening under high-irradiance response conditions as well as a typical phyA germination phenotype under very-low-fluence response conditions, fhl/fhy1 showed no phenotype with respect to the phyA-dependent abrogation of negative gravitropism in blue light and in red-enhanced phototropism, demonstrating clear cytoplasmic functions of phyA. Disturbance of phyA nuclear import in fhl/fhy1 led to formation of FR-induced phyA:GFP cytoplasmic foci resembling the sequestered areas of phytochrome. FHY1 and FHL play crucial roles in phyA nuclear translocation and signaling. Thus the double-mutant fhl/fhy1 allows nuclear and cytoplasmic phyA functions to be separated, leading to the novel identification of cytoplasmic phyA responses.